Cataluña y la difusión del teléfono en España, 1877-1936 - Calvo, Ángel (Cuadernos de Historia Contemporánea, 2008)
Catalonia made a powerful contribution to the diffusion of the telephone in Spain due to its central role in the first transfer of the new technology of the telecommunication and for being the cradle of the most out-standing operators firms. Catalonia as well was the territory where the expansion of the telephone reached higher levels. The article is based on a wide scale of sources both private and public as well as the archives of the Compañía Telefónica Nacional de España and Mancomunidad of Catalonia. The article argues that the differential characteristics of Catalonia are explained by the sum of both private and public initiative, together with its specialization as public agency and private enterprise in different segments of market.